Democratizing Energy, Energizing Democracy: Central Dimensions Surfacing in the Debate - Sorman, Alevgül H.; Turhan, Ethemcan; Rosas-Casals, Marti (Frontiers in Energy Research, 2020)
This perspective piece sets out to contribute to the academic and practitioner debates around energy transitions and democracy initiatives in the age of a climate crisis. For tackling present-day energy challenges in a democratic, equitable and just manner, critical social science and humanities research on meaning and materialities, new actors and narratives, values and democracy is indispensable. In doing so, we centralize our work around three fundamental axes: The Concept, reflecting on the energy itself and revitalizing its essence; The Political, embracing the value laden, political and gendered nature of energy, and recognizing citizens' initiatives as counter currents to centralized energy decision-making; and The People, anticipating the far right’s post-truth narratives that jeopardize planetary futures. We contend that “normative, political and embodied” research and praxis can serve for diversifying the energy transition debate as well as energizing bottom-up community led initiatives in order to democratize the energy playing field of recent times.